Transcriptional regulation of the human CYP46A1 brain-specific expression by Sp transcription factors - Milagre, I. (2015)
Brain defective cholesterol homeostasis has been associated with neurologic diseases, such as Alzheimer's and Huntington's disease. The elimination of cholesterol from the brain involves its conversion into 24(S)-hydroxycholesterol by CYP46A1, and the efflux of this oxysterol across the blood-brain barrier. Herein, we identified the regulatory elements and factors involved the human CYP46A1 expression. Functional 5'deletion analysis mapped a region spanning from nucleotides -236/-64 that is indispensable for basal expression of this TATA-less gene. Treatment of SH-SY5Y cells with mithramycin A resulted in a significant reduction of promoter activity, suggesting a role of Sp family of transcription factors in CYP46A1 regulation. Combination of Sp1, Sp3, and Sp4 over-expression studies in Drosophila SL-2 cells, and systematic promoter mutagenesis identified Sp3 and Sp4 binding to four GC-boxes as required and sufficient for high levels of promoter activity. Moreover, Sp3 and Sp4 were demonstrated to be the major components of the protein-DNA complexes observed in primary rat cortical extracts. Our results suggest that the cell-type specific expression of Sp transcription factors - substitution of Sp1 by Sp4 in neurons - is responsible for the basal expression of the CYP46A1 gene. This study delineates for the first time the mechanisms underlying the human CYP46A1 transcription and thereby elucidates potential pathways underlying cholesterol homeostasis in the brain.